AIDS and insurance law: possible social policy solutions for life insurance applicants excluded due to HIV seropositivity - Theys, Evan Edward (Department of Commercial Law, 2021)
The broad aim of this study is to investigate and recommend a model which would contribute to finding a solution to the AIDS pandemic facing the insurance industry. At present HIV positive persons are excluded from obtaining life insurance, and as a result of this they are excluded from obtaining access to finance as a life insurance policy is a vital financial instrument when attempting to access finance. The insurance industry has decided to protect itself and its response to the pandemic smacks of crisis intervention rather an attempt to find a solution acceptable to all parties. The intention is to investigate the role that all stakeholders, the public sector, the state and the industry can play in contributing to an imaginative response posed by this challenge. This study explores the causes and prognosis of AIDS, how the life insurance industry operates, how necessary life insurance is, strategies adopted by the industry in the face of this challenge, the experience of international insurers, as well as suggesting possible solutions and examining their mechanics. The study also investigates the impact of the Constitution and the Fundamental Rights on the suggested solutions. It recommends a particular solution as a workable model within a social policy perspective. It concludes with a request that all stakeholders participate in this solution for and to the benefit of everyone, as AIDS is not the problem of medical practitioners, or attorneys, or the insurance industry, but a societal problem.